Substance use patterns and awareness of biomedical HIV prevention strategies among sexual and gender minority men in Canada. Issue 12 (1st December 2020) - Card, Kiffer G.; Fournier, Anabelle Bernard; Sorge, Justin T.; Morgan, Jeffrey; Grace, Daniel; Ham, David; Lachowsky, Nathan J.; Trussler, Terry
ABSTRACT: Sexual and gender minority men (SGMM) who use drugs are frequently cited as at-risk for HIV. Fortunately, biomedical prevention can greatly reduce transmission, provided individuals are aware of and interested in the uptake of these strategies. We examined associations between substance use patterns and biomedical prevention among SGMM in Canada. Latent class analysis identified patterns of substance use. Demographic-adjusted logistic regression models assessed the associations between latent classes and key biomedical prevention indicators. Among 669 participants living with HIV (PLWH) and 7, 184 HIV-negative participants, six substance use classes characterized "limited" (46.0%; infrequent/low use of drugs), "common" (31.9%; alcohol, cannabis, and tobacco), "club" (5.2%; alcohol, cocaine, and psychedelics), "sex" (4.8%; alcohol, crystal methamphetamine, GHB, poppers, and erectile drugs), "prescription" (11.0%; alcohol and prescription drugs), and "polydrug" (1.1%; most drugs) use. HIV-negative men in the "prescription" and "sex" substance use classes were more likely to know about the preventive benefits of HIV treatment. All non-"limited use" HIV-negative men were more likely to report interest in taking pre-exposure prophylaxis (PrEP). For PLWH, substance use patterns were not associated with detectable viral loads or treatment awareness. While PLWH exhibited high levels of undetectability and treatment awareness regardless of substance use class, a variety of substance use patterns were associated with increased awareness, interest, and uptake of risk management strategies among HIV-negative participants.